Size, age and otolith morphometrics of Benthosema glaciale collected during IESSNS south of Iceland in July 2020 - Charlotte Sarah Matthews; James Kennedy; Anna H Ólafsdóttir; Christophe Pampoulie (PANGAEA, 2024)
This dataset contains biological measurements and the estimated age of 89 individuals of the North Atlantic myctophid Benthosema glaciale (glacier lantern fish). Individuals were collected opportunistically as bycatch in pelagic trawls (surface and deep) during the Icelandic portion of the International Ecosystem Summer Survey of Nordic Seas (IESSNS) conducted in south Icelandic waters and the Irminger Sea in July 2020. Frozen samples were processed on land in 2022 from five trawl stations located in three IESSNS strata regions (6,11, and 12). Further details on the trawl methodology, sampling and associated environmental variables can be found in related to references and the survey report (Ólafsdóttir and Kennedy, 2020). Observations include multiple length and weight measurements, as well as otolith morphometrics, including otolith length, width and area. Otoliths were photographed on a matte background, proximal side down, and the left otoliths were measured using ImageJ software (if only the right otolith was present, this was used). To age the fish using otoliths, annual rings were counted by two independent readers. If there were inconsistencies in age between them, both readers would confer to reach an agreement, or the otolith was not included in the analysis. The data is provided by the Marine and Freshwater Research Institute (MFRI) in Iceland.